Self-Organizing Multi-Agent System for Management and Planning Surveillance Routes - Rodríguez, Sara; Tapia, Dante. I.; de Paz, Juan F.; Bajo, Javier; Corchado, Juan M.; Abraham, Ajith (Computing and Informatics, 2012)
This paper presents the THOMAS architecture, specially designed to model open multi-agent systems, and its application in the development of a multi-agent system for managing and planning surveillance routes for security personnel. THOMAS uses agents with reasoning and planning capabilities. These agents can perform a dynamic self-organization when they detect changes in the environment. THOMAS is appropriate for developing systems in highly dynamic environments similar to the one presented in this study, as demonstrated by the results obtained after having applied the system to a case study.